Bad Faith : Teachers, Liberalism, and the Origins of McCarthyism - Feffer, Andrew, 1954- (Book collections on Project MUSE., 2019)
This work recounts the history of the Rapp-Coudert investigation into communist subversion in the public schools and municipal colleges of New York City, lasting from 1940 to 1942. This study explores how prominent depression-era liberals, as they joined in accusing Communists of 'bad faith' and branded them enemies of American democracy, anticipated and made McCarthyism possible.